2019
DOI: 10.1186/s12879-019-4206-x
|View full text |Cite
|
Sign up to set email alerts
|

Culturing periprosthetic tissue in BacT/Alert® Virtuo blood culture system leads to improved and faster detection of prosthetic joint infections

Abstract: Background Blood culture bottles (BCBs) provide a semiautomated method for culturing periprosthetic tissue specimens. A study evaluating BCBs for culturing clinical samples other than body fluids is needed before implementation into clinical practice. Our objective was to evaluate use of the BacT/Alert® Virtuo blood culture system for culturing periprosthetic tissue specimens. Methods The study was performed through the analysis of spiked ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
2
22
0
1
Order By: Relevance
“…Moreover, it showed higher sensitivity than conventional culture methods in cases with previous antibiotic treatment since bottles contain antimicrobial removal systems [15,16]. Another advantage is a shorter time for microorganism detection compared to conventional culture methods [12,15]. In our study, all strains except C. acnes, one strain of C. avidum and one strain of S. gordonii grew within the first five days, accounting for 94.6% of positive surgical procedures.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Moreover, it showed higher sensitivity than conventional culture methods in cases with previous antibiotic treatment since bottles contain antimicrobial removal systems [15,16]. Another advantage is a shorter time for microorganism detection compared to conventional culture methods [12,15]. In our study, all strains except C. acnes, one strain of C. avidum and one strain of S. gordonii grew within the first five days, accounting for 94.6% of positive surgical procedures.…”
Section: Discussionmentioning
confidence: 62%
“…Several studies pointed out an improvement of sensitivity of detection of organisms causing PJI compared to conventional culture methods [8,9,10,11]. Recently, Sanabria et al studied BacT/Alert® Virtuo blood culture bottle system and showed it was as slightly more sensitive than conventional methods [12]. Other advantages include a reduced number of specimen required (3 for the most accurate diagnosis in a study performed in 2016) [13], a potential personnel time and labor cost savings [14], and a lower risk of contamination linked to daily inspection of plates.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the drawback of sonicate fluid BCB was the rate of false-positives, which was caused by contamination during the inoculation procedure of BCB with sonicate fluid. Therefore, careful handling is required to minimize contamination [30,31]. Tissue and tissue swab GS were the two least frequently applied intraoperative tests, with a sensitivity of less than 20%.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, three different types of BCB samples were obtained during that study: BCBs inoculated with PJT clinical samples from patients with suspicion of PJI, BCBs inoculated with tissue spiked with bacterial species reported as common microbiological causes of PJI and a negative control which was prepared by inoculating sterilized tissue (irradiated to 25 Gy) from a crushed native femoral head. For further details on the BCB sample preparation method, see Sanabria et al (2019).…”
Section: Sample Collectionmentioning
confidence: 99%
“…Nine of the PJT clinical samples in this study had previously been analyzed using a conventional and a BCB method (Sanabria et al, 2019). Bacterial identification for both methods was done using MALDI-TOF.…”
Section: Identification Of Bacterial Species Reported As Common Causementioning
confidence: 99%